The Impact of Activity Based Learning on Students’ Motivation and Academic Achievement: A study among 12th Grade Science and Environment Students in A Public School in Oman - Albadi, Ahmed (2019)
In recent years, there has been an ongoing debate about the impacts of using activity based learning strategies instead of traditional learning strategies in the classroom, and their appropriateness to increase student’s motivation and attainment. The purpose of this study therefore is to determine the influence of activity based learning on students’ achievement in comparison to passive learning and detect students’ views towards activities. For this purpose, mixed research method was utilized, gathering data from a public school in Oman. Quasi-experimental research design with pre-test and post-test was used in the research with a sample of 24 male students from 12th grade. They were divided into two groups, namely; control and experimental group. The first group received traditional learning and the second group was taught through activity based learning strategy. After that, focus group interviews were held with 8 participants from experimental group to gather qualitative data. Independent sample t-test was used to analyse the quantitative data, whereas content analysis technique was used to analyse qualitative data. The result of the study indicated that activity based learning had a positive effect on students’ achievement. Students believe that activity based learning enhance understanding, increase a sense of responsibility, create attractive learning environment and increase achievement. The study therefore contents that activity based learning has significant impact on student’s academic achievement.